No increased risk of mature B-cell non-Hodgkin lymphoma after Q fever detected: results from a 16-year ecological analysis of the Dutch population incorporating the 2007–2010 Q fever outbreak. (30th March 2022) - Weehuizen, Jesper M; van Roeden, Sonja E; Hogewoning, Sander J; van der Hoek, Wim; Bonten, Marc J M; Hoepelman, Andy I M; Bleeker-Rovers, Chantal P; Wever, Peter C; Oosterheert, Jan Jelrik
Abstract: Background: A causative role of Coxiella burnetii (the causative agent of Q fever) in the pathogenesis of B-cell non-Hodgkin lymphoma (NHL) has been suggested, although supporting studies show conflicting evidence. We assessed whether this association is present by performing a detailed analysis on the risk of mature B-cell NHL after Q fever during and after the largest Q fever outbreak reported worldwide in the entire Dutch population over a 16-year period. Methods: We performed an ecological analysis. The incidence of mature B-cell NHL in the entire Dutch population from 2002 until 2017 was studied and modelled with reported acute Q fever cases as the determinant. The adjusted relative risk of NHL after acute Q fever as the primary outcome measure was calculated using a Poisson regression. Results: Between January 2002 and December 2017, 266 050 745 person-years were observed, with 61 424 diagnosed with mature B-cell NHL. In total, 4310 persons were diagnosed with acute Q fever, with the highest incidence in 2009. The adjusted relative risk of NHL after acute Q fever was 1.02 (95% CI 0.97–1.06, P  = 0.49) and 0.98 (95% CI 0.89–1.07, P  = 0.60), 0.99 (95% CI 0.87–1.12, P  = 0.85) and 0.98 (95% 0.88–1.08, P  = 0.67) for subgroups of diffuse large B-cell lymphoma, follicular lymphoma or B-cell chronic lymphocytic leukaemia, respectively. Modelling with lag times (1–4 years) did not change interpretation. Conclusion: We found no evidence for an association between C. burnetii and NHL after studying the risk of mature B-cell NHL after a large Q fever outbreak in Netherlands.